Feasibility Study on Beef Cattle Development in Teluk Bintuni Regency, West Papua - Trisiwi Wahyu Widayati; Budi Santoso; Djonly Woran; Irba Unggul Warsono; John Arnold Palulungan (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The purpose of this study was to obtain information on the readiness of the development of beef cattle using ranch system in Bintuni District, West Papua through the approach of four local foundations in terms of technical, social and economic. Research respondents were 62 families from four local foundations in Bintuni. Determination of technical feasibility of land used based on carrying capacity for each land. The technical feasibility of raising cattle was observed based on the knowledge of the community. Socio-economic feasibility was investigated based on food security and poverty level of society. Business feasibility was determined according to economic indicators namely B/C ratio, NPV, and IRR. The results showed that the aspect of land provided by the four foundations was feasible with the average carrying capacity based on fresh weight, dry matter and TDN basis were 1.8, 2.0 and 4.5 AU/Ha/year, respectively. About 70,91% of the farmers are free from poverty, and 46.54% are in food security status, which means that cattle raising will not be disturbed by the basic requirement of life but it needs an initial investment to support cattle raising. Based on the technical feasibility of cattle raising as much as 64,39% having no knowledge of breeding, therefore training and livestock education should be done. The business feasibility result shows that cattle raising on a breeding scale of 60 heads were feasible with positive NPV value of IDR 2.536.610,211, IRR of 23.09% and B/C of 1.22. Based on the overall indicators, it was concluded that the development of beef cattle in Bintuni regency was feasible to be done with requisite that improvement on land aspects and community knowledge about raising cattle.